An Econometric Analysis of Carbon Footprints and Life Expectancy in China - Aderemi, Timothy Ayomitunde; Sikwela, Misery M. (International Journal of Energy Economics and Policy, 2025)
China is currently the global largest emitter of greenhouse gases, with a significant portion of its emissions coming from coal-fired power plants and heavy industries. This high level of carbon emissions has not only contributed to global climate change but also to air pollution and respiratory diseases, affecting the health and well-being of the Chinese population. Against this backdrop, this study employed an econometric method to provide an empirical answer to how carbon footprints affected life expectancy in China. The study made use of secondary data from the World Development Indicators, and the data spanning from 2000 to 2021. Consequently, the data was analyzed empirically with the following results: carbon footprint in China experienced a noticeable rise, which persisted till 2020 before it slumped sharply in 2021. Similarly, the carbon footprints had an average value of 5.8 metric tons per capita. On the other hand, on an average basis, life expectancy in China was 78 years. Carbon footprints and life expectancy had a significant positive relationship in the country. Moreover, government health expenditure contributed a significant positive impact to life expectancy in China. Therefore, this study submits that China has been able to increase life span of humans in the face of the current climate change with evidence showing that this may be due to increased resilient health sector.